The presentation of an HIV-1 neutralizing epitope on the surface of major structural protein VP7 of African horse sickness virus - Huismans, H. (Henk), 1942- (University of Pretoria, 2013)
Dissertation (MSc (Genetics))--University of Pretoria, 2005.